Farmers' Willingness to Accept Animal Welfare Practices: A Discrete Choice Experiment with German Pig Producers - Michael Danne; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2022)
Improving the welfare of animals is an important aim in livestock farming. Thereby, farmers' willingness to implement animal welfare practices directly influences the welfare of animals. Therefore, this paper investigates pig farmers' preferences and willingness to accept the implementation of animal welfare practices. We study individual preferences for specific animal welfare measures that are part of a hypothetical animal welfare program. The data are analyzed with a mixed logit model in WTA space and show that German pig farmers require statistically significant compensations for implementing animal welfare practices. We find evidence that farmers' choices are driven by their trust in the consumers' willingness to pay, their evaluation of the efficiency of specific animal welfare practices and farm characteristics. Our results further reveal that accounting for farmers' preferences aids in understanding their willingness to implement specific animal welfare practices. Regarding the improvement of animal welfare these findings are highly relevant for politicians, food industry and producers in order to support animal welfare program design and to identify the costs of welfare improvements on the meat supply chain and future profitability.
Keywords: 330; animal welfare; pig production; farmers' preferences; willingness to accept